The inherited ataxias - Giunti, Paola (Henry Stewart Talks, 2014)
Ataxia, Inherited ataxias, Autosomal dominant cerebellar ataxias (ADCA), ADCA: Clinical classification, Genetic classification, ADCA by mutations, CAGn- age at onset correlation, Common clinical and genetic features, Pathogenesis, Expansion progression, Anticipation, Somatic instability / mosaicism, CAG repeat interruptions in alleles, Interruption/s in modulating disease pathology?, SCA1 project overview, Friedreich’s ataxia, Frataxin protein function, Epigenetic factors in the pathogenesis of FRDA, HDAC inhibition in patient with Friedreich's ataxia, Nicotinamide in patient with Friedreich's ataxia, Phase II open label trial of nicotinamide